Cross-Cultural and Diversity Management Strategy in a Multinational Company - Mirwan Surya Perdhana; Rainda Goesti Rizkita; Susilo Toto Raharjo; Cahyaningratri Cahyaningratri (JURNAL BISNIS STRATEGI, 2022)
The aim of this study is to investigate the correlation of ‘home country’ culture that affects cross-cultural and diversity management strategies. The study used a qualitative method with a phenomenological approach. Cultural framework introduced by Browaeys & Price was utilized to analyze cultural elements. Data collection was conducted through qualitative interviews with foreign expatriates from South Asia region and local Javanese employees who have direct contact with the expatriates. The results showed that, home country cultural background influence the cross-cultural and diversity management strategy in several cultural aspects. There is a strong company value in their managerial activities. It was also found that managers recognize and accept these differences, so that managers see diversity as an advantage.